Dory Fantasmagory : Head in the Clouds - Book 4 - Hanlon, Abby (New York, New York : Dial Books for Young Readers, 2018)
Dory, nicknamed Rascal, has her first loose tooth, but her excitement turns to concern when imaginary evil robber Mrs. Gobble Gracker captures the tooth fairy.
Accelerated Reader AR
Keywords: Readers / Chapter Books; Imagination & Play; Humorous Stories; Junior Fiction